Recurrence plots and their quantifications : expanding horizons : proceedings of the 6th International Symposium on Recurrence Plots, Grenoble, France, 17-19 June 2015 /: expanding horizons : proceedings of the 6th International Symposium on Recurrence Plots, Grenoble, France, 17-19 June 2015. (2016) - Unknown
No abstract available